Current-mode quadrature oscillator based on CCCDTAs with noninteractive dual-current control for both condition of oscillation and frequency of oscillation - Jantakun, Adirek; Jaikla, Winai (My University, 2013)
The realization of 2 current-mode quadrature oscillators using current-controlled current differencing transconductance amplifiers (CCCDTAs) and grounded capacitors is presented. The proposed oscillators can provide 2 sinusoidal output currents with a 90° phase difference. They enable noninteractive dual-current control for both the condition of oscillation and the frequency of oscillation. The high-output impedances of the configurations enable the circuit to be cascaded without additional current buffers. The use of only grounded capacitors is ideal for integration. The circuit performances are depicted through PSpice simulations; they show good agreement to theoretical. © Tübi·tak.
Keywords: CCCDTA; Condition of oscillation; Condition of oscillator; Current-mode; Oscillator